Body mass index and attitudes towards health behaviors among women with endometrial cancer before and after treatment. Issue 2 (15th December 2019) - Harrison, Ross; Zhao, Hui; Sun, Charlotte C; Fu, Shuangshuang; Armbruster, Shannon D; Westin, Shannon Neville; Rauh-Hain, Jose Alejandro; Lu, Karen H; Giordano, Sharon H; Meyer, Larissa A
Abstract : Introduction: Some experts have argued that obesity-related malignancies such as endometrial cancer are a "teachable moment" that lead to meaningful changes in health behaviors. It is unclear if endometrial cancer survivors lose weight following treatment. Our goal with this investigation was to evaluate post-treatment changes in body mass index (BMI) and attitudes towards health behaviors in endometrial cancer survivors. Methods: Incident endometrial cancer cases undergoing surgery between 2009–2015 were identified in the Marketscan Commercial database and linked with BMI data and health behavior questionnaires from the Marketscan Health Risk Assessment database. Patients were excluded for insufficient BMI data. Standard statistical methods, including the two-sample Wilcoxon rank sum test, χ 2 test, and McNemar's test, were used. Results: 655 patients with a median age of 54 (IQR 49-58) were identified and analyzed. Median duration of follow-up was 595 days (IQR 360–1091). Mean pre- and post-treatment BMI was 35.5 kg/m 2 (median 35.0; IQR 27.0–42.3) and 35.6 kg/m 2 (median 34.3; IQR 28.0–42.0), respectively. Median BMI change in the entire cohort was 0 kg/m 2 (IQR −1.0 to 2.0). Weight gain (n=302; 46.1%) or no change in weight (n=106; 16.2%) was seen in most patients. Among the 302 patients who gained weight, the mean pre-treatment BMI was 34.0 kg/m 2 and mean increase was 2.8 kg/m 2 (median 2.0; IQR 1.0–3.4). Among the 247 cases who lost weight, the mean pre-treatment BMI was 38.6 kg/m 2 and mean decrease was 3.2 kg/m 2 (median 2.0; IQR 1.0–4.0). No pre- to post-treatment differences were observed in health behavior questionnaires regarding intention to better manage their diet, exercise more, or lose weight. Discussion: Most endometrial cancer survivors gain weight or maintain the same weight following treatment. No post-treatment changes in attitudes regarding weight-related behaviors were observed. The systematic delivery of evidence-based weight loss interventions should be a priority for survivors of endometrial cancer.